2005
DOI: 10.1590/s1415-47572005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Association of GH and IGF-1 polymorphisms with growth traits in a synthetic beef cattle breed

Abstract: The Canchim beef cattle (5/8 Charolais + 3/8 Zebu) has been selected for meat production in Brazil since late 1950. In the present work the effects of growth hormone (GH) and insulin-like growth factor 1 (IGF-1) polymorphisms were investigated in 688 animals born between 1998 and 2000. These animals belonged to two genetic groups, i.e., traditional and new lineages. Genotype effects on expected breeding values for birth weight (BW), weaning weight (WW) and yearling weight (YW) were investigated by the least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 30 publications
3
48
2
8
Order By: Relevance
“…Visualization of the genotypes of the GH|AluI gene was presented in Figure 3. These results were in line with the study by Pereira et al (2005) by obtaining two genotypes (LL and LV) in Brazilian Canchim cattle. Another study by Curi et al (2006) did not find the VV genotype in Brazilian Zebu cattle and its crosses.…”
Section: Identification Of the Gh Gene Polymorphismsupporting
confidence: 90%
“…Visualization of the genotypes of the GH|AluI gene was presented in Figure 3. These results were in line with the study by Pereira et al (2005) by obtaining two genotypes (LL and LV) in Brazilian Canchim cattle. Another study by Curi et al (2006) did not find the VV genotype in Brazilian Zebu cattle and its crosses.…”
Section: Identification Of the Gh Gene Polymorphismsupporting
confidence: 90%
“…In Angus cattle, these primers produced a frequency of 0.64 for the A allele and 0.36 for the B allele (Ge et al, 2001). Synthetic Canchim breed (5/8 Charolais + 3/8 Zebu) and cows from Simmental and Angus sires and Nellore dams, have low frequencies of the A allele (0.35, 0.2 and 0.32, respectively) compared to the B allele (Curi et al, 2005;Pereira et al, 2005). In our study, similar frequencies were obtained for the two alleles (B allele = 0.542; A allele = 0.463).…”
Section: Discussionmentioning
confidence: 99%
“…The role of IGF-I and its binding proteins has been reviewed (Sara and Hall, 1990;Jones and Clemmons, 1995); IGF-I mediates cell proliferation and is essential for normal development of the mammary gland during puberty and pregnancy (Marshman and Streuli, 2002). Most studies of beef cattle have revealed an association between gene polymorphism and body condition scoring and weight, particularly in early life stages (Ge et al, 2001;Spicer et al, 2002;Curi et al, 2005;Pereira et al, 2005). Significant relationship between milk production and gene character, and a different pattern for corrected 305-day milk productions implies an important physiological role of this somatomedin in other parts of the body.…”
Section: Discussionmentioning
confidence: 99%
“…According to Islam et al (2009), several studies have identified a quantitative trait locus (QTL) associated with carcass traits in the vicinity of IGF1 in beef cattle. Several studies have associated polymorphisms in IGF1 with growth traits in beef cattle as well (Pereira et al, 2005;Andrade et al, 2008). Islam et al (2009) have associated an SNP in the promoter region of IGF1, the same region in which the microsatellite used in this study resides with fat deposition and other carcass traits in crossbred Angus and Charolais beef cattle.…”
Section: Resultsmentioning
confidence: 99%
“…The mean allele substitution effect was 6.9 kg, with the 229 allele associated with reduced YW in this Nelore population. Pereira et al (2005) have investigated the effect of the IGF1 microsatellite studied here on growth traits in a Canchim beef cattle population. The authors found a positive average substitution effect of the IGF1 225-bp allele on birth weight and of the 229-bp allele on YW.…”
Section: Resultsmentioning
confidence: 99%